Given, "(y+xz)p-(x+yz)q = x^{2}-y^{2}".
This equation is of the form "Pp+Qq=R" (Lagrange's linear partial differential equation).
Here, "P = y+xz, Q=-(x+yz), R = x^{2}-y^{2}".
The subsidiary equations are
"\\dfrac{dx}{P}=\\dfrac{dy}{Q}=\\dfrac{dz}{R}\\\\\n\\dfrac{dx}{y+xz}=\\dfrac{dy}{-(x+yz)}=\\dfrac{dz}{x^{2}-y^{2}}~~~~~~~~~~~-(1)".
Each ratio of (1) is equal to "\\dfrac{xdx+ydy}{(x^{2}-y^{2})z} = \\dfrac{dx+dy}{(1-z)(y-x)}".
Let us consider,
"\\dfrac{xdx+ydy}{(x^{2}-y^{2})z} = \\dfrac{dz}{x^{2}-y^{2}}\\\\\nxdx+ydy=zdz\\\\\n\\text{Integrating, }\\\\ \\int xdx + \\int ydy = \\int zdz\\\\\n\\dfrac{x^{2}}{2}+\\dfrac{y^{2}}{2} =\\dfrac{z^{2}}{2}+\\dfrac{c_{1}}{2}\\\\\nx^{2}+y^{2}-z^{2}=c_{1}"
Consider,
"\\dfrac{dx+dy}{(1-z)(y-x)}=\\dfrac{dz}{(x+y)(x-y)}\\\\\n\\dfrac{dx+dy}{1-z}=\\dfrac{dz}{-(x+y)}\\\\\n-(x+y)d(x+y)=(1-z)dz\\\\\n\\text{Integrating,}\\\\\n-\\int (x+y)d(x+y)=\\int (1+z)dz\\\\\n-\\dfrac{(x+y)^2}{2}=\\dfrac{(1-z)^{2}}{-2}+\\dfrac{c_{2}}{2}\\\\\n(1-z)^{2}-(x+y)^{2}=c_{2}"
The general solution is,
"\\phi(c_{1},c_{2})=0\\\\\n\\phi\\left(x^{2}+y^{2}-z^{2}, (1-z)^{2}-(x+y)^{2}\\right)=0."
Comments
Amazing job sir
Leave a comment